Prevalence of non-specifically hemorrhagic or ischemic stroke in the city of Salvador, State of Bahia, Brazil (Research, Society and Development, 2024)
Introduction: Cerebrovascular accident (CVA) is a serious condition that can cause neurological disability and death. It can be hemorrhagic or ischemic. In Brazil, stroke causes around 90 thousand deaths annually. The COVID-19 pandemic may have affected hospital care for these patients. Aim: To understand the prevalence of stroke in Salvador-BA between 2017 and 2021, considering the pre-pandemic period (2017-2019) and post-pandemic period (2020 and 2021). Methodology: Descriptive epidemiological study on the stroke profile between 2017 and 2021, using secondary data from the SUS Hospital Morbidity System (SIH/SUS). Results: During the period, we recorded 10,780 cases of stroke, with a reduction of 10.0% during the pandemic compared to pre-pandemic. The majority of cases were in women, but the prevalence was higher in men. In the age group of 60 to 69 years, there was the highest proportion of cases, with a mortality rate of 11.7%. The age group equal to or over 80 years old had the highest prevalence, corresponding to a mortality rate of 25.1%. Color/race was not registered in 77.8% of cases, with a notable increase among brown and black people in 2020 and 2021, coinciding with the decrease in the proportion of cases without color/race recorded. Conclusion: A decrease in the number of stroke cases was observed during the pandemic, which may indicate difficulties in accessing hospital care. The increase in cases among brown and black people may reflect an improvement in the recording of this data.